1985
DOI: 10.1017/s0022172400062707
|View full text |Cite
|
Sign up to set email alerts
|

Faecal carriage ofClostridium perfringens

Abstract: SUMMARYThe numbers and serotypes of Clostridium perfringens present in the faeces of three groups of hospital patients and young healthy laboratory workers were examined in studies lasting between 10 and 13 weeks.In one hospital some long-stay geriatric patients carried relatively high numbers of C. perfringens (> 107/g) most of the time and it was not unusual in any one week for the majority of these patients to carry the same serotype(s). However, the numbers of C. perfringens in the faeces of young long-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 14 publications
2
8
1
Order By: Relevance
“…However, the long-stay subjects accounted for 71.4 % of the samples where C. perfringens was detected. This is in agreement with the study by Stringer et al (1985), reporting high numbers of C. perfringens in elderly hospitalized patients (Yamagishi et al, 1976;Stringer et al, 1985). It has also been reported that the carriage rate of C. perfringens is significantly higher in the elderly (Benno et al, 1989).…”
supporting
confidence: 91%
“…However, the long-stay subjects accounted for 71.4 % of the samples where C. perfringens was detected. This is in agreement with the study by Stringer et al (1985), reporting high numbers of C. perfringens in elderly hospitalized patients (Yamagishi et al, 1976;Stringer et al, 1985). It has also been reported that the carriage rate of C. perfringens is significantly higher in the elderly (Benno et al, 1989).…”
supporting
confidence: 91%
“…Stringer et al studied faecal carriage of C perfringens in younger and elderly long stay hospital patients and found similar results in five of 21 elderly patients (counts > 10 7 cfu/g). 22 However, the younger long stay patients in the same hospital had faecal counts in the range of 10 3 to 10 4 cfu/ g. These findings are in contrast to the findings reported by Samuel et al 4 None of the control group samples (n = 120) in their study, including those from healthy elderly patients, had faecal counts of C perfringens > 10 3 cfu/g. These conflicting results may be the result of the low numbers of patients recruited in the studies conducted by Yamagishi and colleagues 21 and Stringer et al 22 Therefore, it is essential to detect enterotoxin in faecal samples when attempting to confirm C perfringens as the cause of illness.…”
Section: Diagnosiscontrasting
confidence: 58%
“…All cultures were analysed by serotyping [31][32][33][34]. DNA was prepared as described previously and tested for amplification of fragments of the AE-toxin and enterotoxin genes [35] and by AFLP analysis [26].…”
Section: Perfringens Culturesmentioning
confidence: 99%